Identification, Gene Structure, and Expression of BnMicEmUP: A Gene Upregulated in Embryogenic Brassica napus Microspores - Shahmir, Fariba; Pauls, K. Peter (Frontiers in Plant Science, 2021)
Microspores of Brassica napus can be diverted from normal pollen development into embryogenesis by treating them with a mild heat shock. As microspore embryogenesis closely resembles zygotic embryogenesis, it is used as model for studying the molecular mechanisms controlling embryo formation. A previous study comparing the transcriptomes of three–day-old sorted embryogenic and pollen-like (non-embryogenic) microspores identified a gene homologous to AT1G74730, of unknown function that was upregulated 8 fold in the embryogenic cells. In the current study, the gene was isolated and sequenced from B. napus and named BnMicEmUP (B. napus microspore embryogenesis up regulated gene). Four forms of BnMicEmUP mRNA and three forms of genomic DNA were identified.BnMicEmUP2,3 was up-regulated more than seven-fold by day 3 in embryogenic microspore cultures compared to non-induced cultures. BnMicEmUP1,4 was highly expressed in leaves. Transient expression studies of BnMicEmUP2,3::GFP fusion protein in Nicotiana benthamiana and in stable Arabidopsis transgenics showed that it accumulates in chloroplasts. The features of the BnMicEmUP protein, which include a chloroplast targeting region, a basic region and a large region containing 11 complete leucine-rich repeats, suggest that it is similar to a bZIP PEND (plastid envelope DNA-binding protein) protein, a DNA binding protein found in the inner envelope membrane of developing chloroplasts. Here we report that the BnMicEmUP2,3 overexpression in Arabidopsis increases the sensitivity of seedlings to exogenous ABA. The BnMicEmUP proteins appear to be transcription factors that are localized in plastids and are involved in plant responses to biotic and abiotic environmental stresses ; as well as the results obtained from this study can be used to improve crop yield